2004
DOI: 10.1002/ddr.10382
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the anti‐platelet actions of FK419, a novel non‐peptide antagonist of platelet GPIIb/IIIa

Abstract: The anti-platelet properties of FK419 ((S)-2-acetylamino-3-[(R)- [1-[3-(piperidin-4-yl)propionyl]piperidin-3-ylcarbonyl] amino]propionic acid), a novel non-peptide GPIIb/IIIa antagonist, were compared in a variety of experimental settings, both in vitro and in vivo, with other GPIIb/IIIa antagonists including xemilofiban, lamifiban, tirofiban, and FK633. Receptor binding studies suggested that FK419 had potent GPIIb/IIIa antagonistic activity that is comparable with those of reference antagonists. FK419 effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…We recently reported that FK419 dose-dependently prevented the reocclusion of MCA after recanalization in photothrombotic MCA occlusion model in guinea-pigs (Moriguchi et al , 2004 a ). FK419 was found not only to prevent reocclusion but also to thrombolyse the obstructive thrombus in a similar model (Moriguchi et al , 2004 b ; Moriguchi et al , 2005). However, the clinical predictive value of this model is limited because numerous compounds that were active in rodent models have failed in clinical trials.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We recently reported that FK419 dose-dependently prevented the reocclusion of MCA after recanalization in photothrombotic MCA occlusion model in guinea-pigs (Moriguchi et al , 2004 a ). FK419 was found not only to prevent reocclusion but also to thrombolyse the obstructive thrombus in a similar model (Moriguchi et al , 2004 b ; Moriguchi et al , 2005). However, the clinical predictive value of this model is limited because numerous compounds that were active in rodent models have failed in clinical trials.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, abciximab, an antibody directed to GPIIb/IIIa receptor, was found to have beneficial effects in acute ischemic stroke (AbESTT Investigators, 2003). FK419 ((S)-2-acetylamino-3-[(R)-[1-3-(piperidin-4-yl)propionyl]piperidin-3-ylcarbonyl]amino]propionic acid trihydrate) is a novel nonpeptide GPIIb/IIIa receptor antagonist with strong antiplatelet efficacy (Mihara et al , 2004). Furthermore, it has been demonstrated that FK419 effectively dispersed aggregating platelets and improved neurologic deficits and reduced brain damage in guinea-pig thrombotic middle cerebral artery (MCA) occlusion model (Moriguchi et al , 2004 b ).…”
Section: Introductionmentioning
confidence: 99%
“…FK419 [15], FK633 [16], FR184764, FR233229, FR231643, lamifiban [17], xemilofiban [18], and tirofiban [19] (Fig. 1) were synthesized in Fujisawa Pharmaceutical Co., Ltd (Osaka, Japan), with purity >98% by HPLC and mass spectrum analysis.…”
Section: Methodsmentioning
confidence: 99%
“…GPIIb/IIIa antagonists are expected to be effective in these phenomena, and abciximab, a monoclonal anitibody, and tirofiban, a nonpeptide antagonist, have been clinically evaluated for their efficacy in acute stroke patients (Junghans et al , 2002; AbESTT Investigators, 2003; Seitz et al , 2003; Straub et al , 2004). We have recently identified FK419 (( S )-2-acetylamino-3-[( R )-[1-[3-(piperidin-4-yl) propionyl]piperidin-3-ylcarbonyl]amino]propionic acid trihydrate) as a novel nonpeptide GPIIb/IIIa antagonist with high affinity for the GPIIb/IIIa complex (Mihara et al , 2004). Selective ligand inhibition by FK419 enabled almost complete inhibition of platelet aggregation without prolongation of bleeding time in dogs (Aoki et al , unpublished observation).…”
Section: Introductionmentioning
confidence: 99%